UPAYA MENINGKATKAN KESEHATAN IBU DAN ANAK MELALUI PROGRAM LITERASI KESEHATAN DAN HIBAH BUKU DI DESA CINTAMULYA RW 05 JATINANGOR - Fitri Perdana; Heti Herawati (Universitas Padjadjaran, 2018)
ABSTRACT Woman, especially a mother, plays a very important role in family health. This happens because a mother tends to have greater attention to her family's health condition. Mother's concerns range from adopting a healthy lifestyle, providing healthy and fresh food, cooking nutritious food, washing clothes, cleaning the house and many other things that a mother always does. Especially with regard to family domestic work activities. With so many responsibilities and activities a mother to maintain family health, sometimes make him forget his own health. Though the health of a mother is very important in maintaining and improving the quality of family health. The Purpose of Dedication to the Sports Society of Arts and Creativity is to provide awareness and information on the importance of maintaining health for mothers and children so as to improve aspects of development, especially in terms of health. Methods conducted are qualitative: observation, observation, interview, literature study and triangulation data. The result, based on the results of observation, area mapping and interviews indicate the existence of community needs related health literacy for mother and child. For this purpose, a program of extension is conducted on how to maintain the health of mothers and children with the speakers of a health expert, and books grant program is held so that mothers can continue to update the health-related knowledge of the books as well as storybooks for children, children, in an effort to foster interest in reading the children of Cintamulya village from childhood. Because the interest of reading that must be started since childhood. In conclusion, that with this health literacy program, began to open awareness and add information about the importance of maintaining health,